Gegar Bahasa pada Program Pertukaran Mahasiswa Indonesia di Jepang: Sebuah Studi Kasus - Siti Yulidhar Harunasari; Nurhasanah Halim (Universitas Mulawarman, 2021)
The purpose of this study was to describe the experience of a language learner in an Indonesian student exchange program in Japan aimed to enable students to learn the language and culture directly in their home country. This experience was captured through a descriptive case study conducted to obtain a clear picture of what happened and find out what aspects could cause language concussion; and how the influence of language shock on the social acculturation of language learners. Data were collected through observation and interviews. The results showed that the language shock experienced by the Research Subjects in the target language environment included linguistic aspects at the phonological and morphological levels. Sociolinguistic aspects at the level of the use of a variety of respect. Anxiety also occurs due to the loss of signs and symbols of social relationships commonly known by the Research Subjects. Therefore, cultural differences between Indonesia and Japan should be anticipated so as not to cause difficulties in carrying out social acculturation.